MENCEGAH RADIKALISME MELALUI MODERASI BERAGAMA : (STUDI KASUS FORUM KERUKUNAN UMAT BERAGAMA KABUPATEN CIAMIS) - Novi Dwi Nugroho; Daniel Rabitha; Ismail (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
As evidenced by the events that occurred in 2021, extremist ideology is still prevalent among religious devotees in Indonesia. Many groups working under the leadership of the government have made efforts to reduce this radical ideology, one of which being the Forum for Religious Harmony (FKUB). Aside from that, the Religious Harmony Forum was tasked with conducting a research to develop a strategy for defeating radicalism based on religious moderation. In this qualitative study, data mining was done through in-depth interviews, observations, and document studies on the management of FKUB Ciamis and the community. The research findings indicate that each representative of the religious assembly at FKUB has a reasonable religious understanding, which is evident in their attitude of respecting each other's religious beliefs and giving comfort for diverse persons in worship. To combat the ideology of radicalism, two techniques can be used: first, educate the public by conducting outreach on the importance and operationalization of moderate views in social relations. Second, the operation of religious organizations such as FKUB, which play a significant role in promoting religious unity.